ANALISIS PENGENDALIAN KUALITAS PRODUK BAKPIA JOGKEM ALUN-ALUN KIDUL YOGYAKARTA - Rayhan Akbar Pratama; Anggraeni, Rini; Lintia Putri Nanda (Fakultas Pertanian Universitas Janabadra, 2025)
Consistent product quality is crucial for maintaining competitiveness in the competitive bakpia (bakpia) industry. This study aims to analyze defect rates, identify dominant defect types, and evaluate the stability of the production process at the Bakpia Jogkem, Alun-alun Kidul, Yogyakarta, Micro, Small, and Medium Enterprises (MSMEs), as a case study. This study used a quantitative approach through Statistical Quality Control (SQC) tools, including a Pareto Diagram for problem prioritization and a Control Chart (P-Chart) for stability analysis. The analysis concluded that the production process operates at a 1% defect rate and is in statistical control. The Pareto Diagram identified two major defects classified as the vital few: